2017
DOI: 10.3390/su10010005
|View full text |Cite
|
Sign up to set email alerts
|

Green Suppliers Performance Evaluation in Belt and Road Using Fuzzy Weighted Average with Social Media Information

Abstract: A decision model for selecting a suitable supplier is a key to reducing the environmental impact in green supply chain management for high-tech companies. Traditional fuzzy weight average (FWA) adopts linguistic variable to determine weight by experts. However, the weights of FWA have not considered the public voice, meaning the viewpoints of consumers in green supply chain management. This paper focuses on developing a novel decision model for green supplier selection in the One Belt and One Road (OBOR) initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Ho et al [41] concluded that the most common criteria of supplier selection decision-making processes were quality, cost, management, technology, and flexibility. Kuo-Ping Lin et al [42] built a supplier selection process based on six main criteria. Peng Jia et al [43] have pointed out in the literature review that the framework has developed including economic, environmental, and social sustainability criteria.…”
Section: Application Of Mcdm Methods In Supplier Selection Processesmentioning
confidence: 99%
“…Ho et al [41] concluded that the most common criteria of supplier selection decision-making processes were quality, cost, management, technology, and flexibility. Kuo-Ping Lin et al [42] built a supplier selection process based on six main criteria. Peng Jia et al [43] have pointed out in the literature review that the framework has developed including economic, environmental, and social sustainability criteria.…”
Section: Application Of Mcdm Methods In Supplier Selection Processesmentioning
confidence: 99%
“…Liu et al [149] investigated the green supplier selection problem by combining QFD with partitioned Bonferroni mean operator in the context of interval type-2 fuzzy environment. In addition, the fuzzy weighted average operator [152], the 2-tuple ordered weighted averaging (TOWA) operator [153], the hesitant fuzzy Hamacher power weighted average (HFHPWA) operator [150], the interval-valued intuitionistic fuzzy geometric weighted Heronian means (IVIFGWHM) operator [151], and the single-valued triangular neutrosophic Dombi prioritized normalized Bonferroni mean (SVTNDPNBM) operator [154] have been employed for evaluation and selection of the best supplier in green supply chain management.…”
Section: Aggregation Operator-based Methodsmentioning
confidence: 99%
“…Technology level [23,27,46,74,81,98,99,110,120,123,124,135,143,148,149,152,169,175,180,189,191,199,204,208]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Deng et at. [11] developed multiple attribute decision making (MADM) with some 2-tuple linguistic Pythagorean fuzzy Hamy mean operators. Wang et al [12] developed an MADM model with interval-valued 2-tuple linguistic Pythagorean fuzzy information.…”
Section: Literature Reviewmentioning
confidence: 99%